ANALISIS NILAI MORAL PADA LIMA CERPEN KARYA KUNTOWIJOYO DALAM BUKU DILARANG MENCINTAI BUNGA-BUNGA - Wasi'ah, Dede; Saripah, Tuti; Stiyanti, Dela Wahyu; Mustika, Raden Ika (IKIP Siliwangi, 2018)
This study aims to analyze the moral values contained in five short stories by Kuntowijoyo in a collection of short stories recorded in a book titled